Uşak Şehrinde Okullara Erişebilirliğin Coğrafi Bilgi Sistemleri (CBS) İle Analizi / Analysis of Accessibility of Schools in Uşak City via Geographical Information Systems (GIS) - Sezer, Adem; Deniz, Mehmet; Topuz, Mustafa (Journal of History Culture and Art Research, 2018)
Abstract Towards the end of the 20th century, technologically advanced societies have linked the infrastructure and service sectors of the city with technology to reduce population pressure on cities and to sustain welfare. With this aim, state and city managers aimed to accelerate the operation of services. This situation has led to the establishment of the basics for the creation of smart cities. The areas of use of spatial analysis have also increased with the developing smart city systems. When spatial analyzes are associated with GIS, it becomes very useful for urban studies. Accessibility to schools in the city of Uşak is also an example of this type of spatial analysis. In the study, accessible areas were determined by applying network analysis to the schools in Uşak city. While the data set used in the analysis was created, the locations of the schools taken from Uşak Provincial Directorate of National Education, the number of students, teachers and classrooms, the road and building data obtained from the zoning plan of Uşak Municipality, and the OpenStreetMap vector data were used. In addition, population data of the study area were obtained from TURKSTAT by age. The analysis was applied to the distances and alternative distances specified in the law and the accessable areas were determined. As a result of the study, it was determined that the biggest problem in accessibility was in kindergartens. As far away from the center as primary and secondary schools, problems were observed in the walls of the city. In high schools, almost all the city remains within the domain. Considering the adequacy of the educational institutions, it is observed that there are a large number of students per teacher and classroom in kindergartens. Öz 20. yüzyılın sonlarına doğru teknolojik açıdan ilerleyen toplumlar şehirlerin üzerinde oluşan nüfus baskısını azaltmak ve refahı sürdürülebilir kılmak için şehrin altyapı ve hizmet sektörlerini teknoloji ile ilişkilendirmişlerdir. Bu gaye ile devlet ve kent yöneticileri hizmetlerin işleyişini hızlandırmayı amaçlamışlardır. Bu durum akıllı kentlerin oluşmasına zemin hazırlayan çalışmaların yapılmasına sebep olmuştur. Gelişen akıllı kent sistemleri ile mekânsal analizlerin kullanım alanları da artmıştır. Mekânsal analizler CBS ile ilişkilendirildiğinde kent çalışmaları için oldukça kullanışlı hale gelmektedir. Çalışmanın amacını da oluşturan Uşak şehrindeki okullara erişilebilirlik bu tipteki mekânsal analizlere bir örnektir. Çalışmada Uşak şehrinde bulunan eğitim kurumlarına network(ağ) analizi uygulanarak erişilebilir alanlar belirlenmiştir. Analizde kullanılan veri seti oluşturulurken Uşak İl Milli Eğitim Müdürlüğünden alınan eğitim kurumlarının konumları, öğrenci, öğretmen ve derslik sayıları, Uşak Belediyesinden alınan imar planından elde edilen yol ve yapı verileri ile OpenStreetMap vektör verilerinden faydalanılmıştır. Ayrıca çalışma sahasının yaş çağlarına göre nüfus verisi TÜİK’ten temin edilmiştir. Analiz yasalarda belirtilen mesafelere ve alternatif mesafelere uygulanarak erişebilir alanlar belirlenmiştir. Çalışma sonucunda erişebilirlikte en büyük problemin anaokullarında olduğu belirlenmiştir. İlkokul ve ortaokullarda merkezden uzaklaştıkça şehrin çeperlerinde problemlerin olduğu görülmüştür. Liselerde ise hemen hemen bütün şehir etki alanı içerisinde kalmaktadır. Eğitim kurumlarının yeterliliğine bakıldığında yine anaokullarına öğretmen ve derslik başına düşen öğrenci sayılarının fazla olduğu göze çarpmaktadır.